Open science practices at state institutes and quality assurance institutions—opportunities and challenges at the interface between science and practice Open-Science-Praktiken an Landesinstituten und Qualitätseinrichtungen der Länder – Chancen und Herausforderungen an der Schnittstelle zwischen Wissenschaft und Praxis - Birnbaum, Lisa; Dehmel, Alexandra; Fröhlich, Nora; Norwig, Kerstin; Rutsch, Juliane; Rangel, Ulrike; Fauth, Benjamin (Zeitschrift für Erziehungswissenschaft, 2026)
The gap between educational research, practice, administration, and policy—often referred to as the research-practice gap—presents a major challenge for the education system. In Germany, this gap is being addressed by (federal) state-level educational institutes and quality agencies (LI/QE), which act as intermediary actors within the educational ecosystem. These institutions play a key role in supporting evidence-based decision-making, particularly through the provision of data and scientific findings. Open Science Practices can enhance the accessibility and transparency of such data and knowledge for various stakeholders. Drawing on the experience of the Institute for Educational Analyses Baden-Württemberg (IBBW), this article illustrates how Open Methodology, Open Educational Resources, Open Data, and Open Access can be implemented in practice. We highlight the potential of Open Science to reduce the research-practice gap, as well as specific challenges faced by LI/QE in this context.
CRIS-Team Scopus Importer:2026-04-10
Keywords: Evidence-based policy; Evidence-based practice; Open Science; Research-practice gap; State-level educational institutes